Quality Enhancement of Probiotic Yogurt Parijoto Fruit (Medinilla speciosa) Fortification Physicochemical, Microbiological, Structural, and Sensory Evaluation - Kusuma, Valentina Carladhea; Maula, Agnis Dianatul; Sumbaga, Nariswari Prabaswara; Dewi, Cecilia Shinta; Radiati, Lilik Eka; Armaini (Faculty of Animal Science Universitas Brawijaya, 2026)
The increasing consumption of dairy products in Indonesia is often limited by the short shelf life and low stability of fresh milk. One strategy to improve the functional value of dairy products is by processing milk into probiotic yogurt and enriching it with natural bioactive ingredients. Parijoto fruit (Medinilla speciosa), an indigenous Indonesian plant rich in phenolic compounds, flavonoids, anthocyanins, and minerals, has strong potential as a functional additive in fermented dairy products. This study aimed to evaluate the effect of parijoto fruit puree on the physicochemical and microbiological characteristics of probiotic yogurt. The experiment used a Completely Randomized Design (CRD) with five levels of parijoto puree (0%, 5%, 10%, 15%, and 20%) and four replications. Observed parameters included pH, titratable acidity, moisture content, protein content, total lactic acid bacteria (LAB), color characteristics, as well as microstructure and mineral profile using FESEM-EDS analysis. Results showed that parijoto puree significantly affected pH, titratable acidity, color, and total LAB, but did not significantly influence moisture content. Increasing concentrations decreased pH and increased acidity due to organic acids in the fruit. Protein content tended to decline at higher concentrations, while LAB counts decreased, likely due to antimicrobial compounds such as flavonoids and tannins. Color intensity, especially redness, increased with higher concentrations because of anthocyanin pigments. Microstructural analysis indicated a more compact gel network at moderate concentrations, while mineral analysis confirmed the presence of essential elements such as Ca, K, P, Mg, and Na. In conclusion, parijoto fruit puree improves yogurt characteristics and has potential as a functional ingredient.